Team trust and performance in pediatric trauma. Issue 1 (September 2020) - Coppola, Sarah; Webster, Kristen; Gurses, Ayse
Pediatric trauma cases involve multiple healthcare workers and a complicated coordination of care. The differing roles and changing hospital schedules means that trauma teams are constantly changing and each trauma case may involve a new team. Trust in these dynamic, high stakes environment is important for team performance. A survey on team trust, psychological safety, and team learning behavior was circulated by email to all roles that respond to the highest level trauma at a large, Midatlantic, level 1 pediatric trauma center. Seventy-seven participants responded and represented the emergency department, pediatric intensive care unit, surgery, respiratory therapy, pharmacy, technician, child life, social work, and spiritual care. The respondents generally scored high on measures of psychological safety; however, the majority (69%) did not agree that it was safe to take a risk on the team. Similarly, the respondents scored high on measures of team trust. Measures of team learning varied with the majority responding neither agree nor disagree on "In this team, someone always makes sure that we stop to reflect on the team's work process, " "People in this team often speak up to test assumptions about issues under discussion, " and "We invite people from outside the team to present information or have discussions with us". The results show that these responses also vary by role and home department, but these differences were not statistically significant. Understanding current perceptions of team trust and learning will allow for targeted interventions to improve team communication and performance in pediatric trauma.